2014
DOI: 10.1155/2014/605914
|View full text |Cite
|
Sign up to set email alerts
|

Xiao Yao San Improves Depressive‐Like Behaviors in Rats with Chronic Immobilization Stress through Modulation of Locus Coeruleus‐Norepinephrine System

Abstract: Most research focuses on the hypothalamic-pituitary-adrenal (HPA) axis, hypothalamus-pituitary-thyroid (HPT) axis, and hypothalamus-pituitary-gonadal (HPGA) axis systems of abnormalities of emotions and behaviors induced by stress, while no studies of Chinese herbal medicine such as Xiao Yao San (XYS) on the mechanisms of locus coeruleus-norepinephrine (LC-NE) system have been reported. Therefore, experiments were carried out to observe mechanism of LC-NE system in response to chronic immobilization stress (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…Of note, AT-I treatment significantly reduced these changes, as evidenced by increased sucrose preference as well as shortened immobility time in FST and TST. Of note, plenty of studies have confirmed that Xiaoyao San, a well-known traditional Chinese formula containing Rhizoma Atractylodis macrocephalae exerted anti-depressant-like effects in an animal model of CUMS-induced depression (21,22) and perimenopausal women with depression (23). In addition, a study by Zhou et al (16) identified that AT-I may be the component of Xiaoyao San responsible for its anti-depressant effects.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, AT-I treatment significantly reduced these changes, as evidenced by increased sucrose preference as well as shortened immobility time in FST and TST. Of note, plenty of studies have confirmed that Xiaoyao San, a well-known traditional Chinese formula containing Rhizoma Atractylodis macrocephalae exerted anti-depressant-like effects in an animal model of CUMS-induced depression (21,22) and perimenopausal women with depression (23). In addition, a study by Zhou et al (16) identified that AT-I may be the component of Xiaoyao San responsible for its anti-depressant effects.…”
Section: Discussionmentioning
confidence: 97%
“…33) Moreover, the mechanism may be related to the mediation of neurosteroid synthesis, 34) the modulation of the locus coeruleus-norepinephrine system, 35) and the serum levels of 5-HT, brain derived neurotrophic factor (BDNF), CORT and interleukin-6.…”
Section: )mentioning
confidence: 99%
“…Accumulated evidence has shown that Xiaoyaosan, a traditional Chinese herbal formula, exerts antidepressant effects via improving the core symptoms of behavioral despair and anhedonia . Xiaoyaosan has been prescribed to treat mental disorders for thousands of years in China and was originally recorded in Taiping Huimin Heji Jufang , the first official compilation of materia medica around the world during the Song Dynasty in China (960–1127 AD).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Accumulated evidence has shown that Xiaoyaosan, a traditional Chinese herbal formula, exerts antidepressant effects via improving the core symptoms of behavioral despair and anhedonia. [6][7][8][9] Xiaoyaosan has been prescribed to treat mental disorders for thousands of years in China 6,10 and was originally recorded in Taiping Huimin Heji Jufang, the first official compilation of materia medica around the world during the Song Dynasty in China (960-1127 AD). In our previous studies, we discovered that Xiaoyaosan and its modified formulas might ameliorate hypothalamic-pituitary-adrenal hyperactivity, reverse neurotrophic abnormalities, and maintain the internal homeostasis of the kynurenine/serotonin pathway.…”
Section: Introductionmentioning
confidence: 99%